Análisis de la reforma tributaria en el período 2021–2022 y su incidencia en la recaudación del impuesto a la renta de los contribuyentes no obligados a llevar contabilidad de la provincia de Cotopaxi. - Pillo Toaquiza, Gladys Del Consuelo (2023)
The changes in the tax reform generated an increase in income tax collection from taxpayers not obliged to keep accounting records in the province of Cotopaxi in the year 2021-2022. The research project studied the analysis of the changes of the tax reform and its impact on the income tax collection of taxpayers not obliged to keep accounting records in the province of Cotopaxi in the period 2021 - 2022, in such a way that descriptive research was carried out applying a quantitative approach to analyze the information provided by the Internal Revenue Service, In which the different economic activities of the taxpayers were evidenced, a total of 4560 taxpayers not obliged to keep accounts in the year 2022 were established, which represent an increase of the Income Tax in numerical values of $ 2,760,576.28 to $ 2,760,576.28 in the year 2022. 2,760,576.28 compared to the collection of the year 2021 with a total of $ 808,536.93. Finally, it was concluded that the change in the tax reform generated an increase due to the new calculation of the income tax base, generating an increase of 71%, which represents in monetary value $1,952,039.35 in the calculation of the income tax for the period 2022.